Aliphatic bio-oils from corks: A Py–GC/MS study - Marques, António Velez; Pereira, Helena (Journal of Analytical and Applied Pyrolysis, 2014)
Cork samples from Betula pendula, Quercus suber and Quercus cerris were submitted to Py–GC–MS/FID at temperatures between 550°C and 900°C and the pyrolysis-derived compounds (py-products) were identified and quantified. Corks were compared with wood samples. Py-products include suberin, lignin and carbohydrates derivatives. Suberin py-products are dominated by unsaturated aliphatics. Corks pyrolysis yield and composition were dramatically influenced by temperature in contrast to wood that showed stable results across temperatures. At 850–900°C the peaks area of cork pyrograms were approximately two times higher than at 550°C, for which yield was about half of the woods, and cork py-products were dominated by suberin-derived short chain aliphatics, namely 1-alkenes, while at 550°C composition was dominated by lignin derivatives. Lignin and carbohydrate derived products decreased dramatically over 750°C while the opposite was observed for unsaturated aliphatics. Cork materials show a high potential as feedstock for production of aliphatic-rich pyrolytic biofuels or as a source of olefins.
Keywords: Bark; Bio-oil; biomass; Cork; pyrolysis; suberin

Lignin monomeric composition of corks from the barks of Betula pendula, Quercus suber and Quercus cerris determined by Py–GC–MS/FID - Marques, António Velez; Pereira, Helena (Journal of Analytical and Applied Pyrolysis, 2012)
Samples of cork tissues separated from the barks of Betula pendula, Quercus suber and Quercus cerris were characterized by Py–GC–MS/FID in respect to composition of lignin. The pyrolysis temperature influenced the yield of pyrolysis products, and in the conditions usually applied to wood pyrolysis (550 ◦C) suberin is only partially degraded into products. The lignin composition of the three corks showed predominantly a guaiacyl-based lignin: guaiacyl (G) units represented 85.7%, 96.4% and 93.7% of lignin respectively in B. pendula, Q. suber and Q. cerris corks, while syringyl (S) units amounted respectively to 11.9%, 2.5% and 2.7% and p-hydroxyphenyl (H) units to 2.4%, 1.1% and 3.6%. Pyrolysis of the woods of these same species confirmed the GS character of their lignins in contrast to the corks G-lignin type. The influence of ferulic acid in the results and its integration in a heterogeneous cork lignin structure was discussed.
Keywords: Betula pendula; Cork; Lignin composition; pyrolysis; Quercus cerris; Quercus suber

Thermogravimetric analysis of Mediterranean plant species - a.P. Dimitrakopoulos (Journal of Analytical and Applied Pyrolysis, 2001)
Twelve dominant Mediterranean plant species were subjected to thermogravimetric analysis (TGA) in air medium, in order to study their thermal degradation process and assess their potential combustibility as natural fuels. Statistically signiﬁcant differences were observed among the values of the pyrolytic parameters of the species analyzed. The mean volatilization rate values resulted in meaningful ranking of the species into vegetation types of similar combustibility, as veriﬁed by observations during actual wildﬁres. The use of TGA as a method for assessing the combustibility of individual plant species seems justiﬁed
Keywords: combustibility; lignocellulosic materials; Mediterranean; natural fuels; pyrolysis; thermogravimetric analysis; wildland fires

Thermogravimetric analysis of Mediterranean plant species - a. P. Dimitrakopoulos (Journal of Analytical and Applied Pyrolysis, 2001)
Twelve dominant Mediterranean plant species were subjected to thermogravimetric analysis (TGA) in air medium, in order to study their thermal degradation process and assess their potential combustibility as natural fuels. Statistically signiﬁcant differences were observed among the values of the pyrolytic parameters of the species analyzed. The mean volatilization rate values resulted in meaningful ranking of the species into vegetation types of similar combustibility, as veriﬁed by observations during actual wildﬁres. The use of TGA as a method for assessing the combustibility of individual plant species seems justiﬁed
Keywords: combustibility; lignocellulosic materials; Mediterranean; natural fuels; pyrolysis; thermogravimetric analysis; wildland fires

Thermal decomposition of wood in oxidizing atmosphere. A kinetic study from non-isothermal TG experiments - Cordero, T; Rodriguez-Maroto, J M (Thermochimica acta, 1991)
The kinetics of thermal decomposition of four wood species in oxygen-bearing atmo- spheres of 5, 10 and 20% molar Oz concentrations have been studied from temperature-pro- grammed experiments carried out at 5, 10 and 20 K mm ’ -* heating rate. Devolatihzation as weII as combustion of the reaminin g solid have been considered to analyze the weight loss curves. The homogeneous volume reaction (VR) model has been used to describe devolatihza- tion, whereas for solid combustion the grain model has been also checked. A two-stage approach has been used to fit the conversion-time curves and to derive the corresponding apparent kinetic parameters. The VR/VR (pyrolysis/combustion) combination provided a better description of the experimental (~-1 curves than the VR/grain combination. Hohn oak and cork oak showed very close reactivities, whereas some differences were observed for aleppo pine and eucalyptus.
Keywords: Aleppo pine; combustion (voyant); Cork oak; EUCALYPTUS; Holm oak; Kinetic model; pyrolysis; Wood

PYROLYSIS OF HOLM OAK AND OLIVE WOOD - Figueiredo, J L (International Conference on Biomass for Energy and Industry, 1989)
The pyrolysis of olive and holm-oak wood to produce charcoal and fuel gas was studied in the temperature range from 3 00 to 9 00°C. The charcoals were characterized by proximate and ultimate analyses, and the gases were analyzed chromatographycally The fised carbon content of the charcoal increased with temperature up to 600-700°C and then remained essentially constant. The gases produced were mainly CO, CO , H and CH . The composition of the pyrolysis gas produced at each temperature was determined, and its heating value was calculated. Taking into consideration the quality of the charcoal and the heating value of the gases produced, it can be concluded that the optimal pyrolysis temperature is 600'C.
APS
Keywords: charcoal production; fuel gas; Holm oak; olive; pyrolysis

Pyrolysis of holm-oak wood: influence of temperature and particle size - Figueiredo, J L; Valenzuela, C; Bernalte, A; Encinar, J M (Fuel, 1989)
The pyrolysis of holm-oak wood sawdust was studied to determine the characteristics of the charcoal and the nature and amounts of gases produced. The temperature was varied from 300 to 900 °C and the wood particle size from 0.40 to 2 mm diameter. The fixed carbon content of the charcoal increased with temperature up to 700 °C, and then remained essentially constant. The gases produced were mainly CO, CO2, H2 and CH4. The rate constants and activation energies for the production of each gas were calculated assuming first order kinetics. The composition of the pyrolysis gas produced at each temperature was determined, and its heating value was calculated. Taking into consideration the quality of the charcoal and the heating value of the gases produced, it can be concluded that the optimal pyrolysis temperature is ≈ 600 °C.
Keywords: charcoal; Particle Size; pyrolysis

Pyrolysis of holm-oak wood: influence of temperature and particle size - Figueiredo, J. L.; Valenzuela, C.; Bernalte, A.; Encinar, J. M. (Fuel, 1989)
The pyrolysis of holm-oak wood sawdust was studied to determine the characteristics of the charcoal and the nature and amounts of gases produced. The temperature was varied from 300 to 900 °C and the wood particle size from 0.40 to 2 mm diameter. The fixed carbon content of the charcoal increased with temperature up to 700 °C, and then remained essentially constant. The gases produced were mainly CO, CO2, H2 and CH4. The rate constants and activation energies for the production of each gas were calculated assuming first order kinetics. The composition of the pyrolysis gas produced at each temperature was determined, and its heating value was calculated. Taking into consideration the quality of the charcoal and the heating value of the gases produced, it can be concluded that the optimal pyrolysis temperature is ≈ 600 °C.
Keywords: charcoal; Particle Size; pyrolysis

Influence of particle size and pyrolysis conditions on yield, density and some textural parameters of chars prepared from holm-oak wood - Valenzuela-Calahorro, C; Bernalte-Garcia, A; Gómez-Serrano, V; Bernalte-García, Ma.J. (Journal of Analytical and Applied Pyrolysis, 1987)
Chars were prepared from holm-oak wood (Quercus ilex) using sawdust, cubes (20 × 20 × 20 mm) and octagonal prisms (20 × 20 × 80 mm) by heating in nitrogen under dynamic (sawdust and cubes) and isothermal (sawdust and prisms) conditions to different final temperatures. The yield of char production depends on the wood particle size, heating rate and final temperature. The density of the chars as measured by helium displacement, ϱHe (g/cm3), is influenced by the wood particle size and heating conditions. Chars prepared from holm-oak wood are essentially microporous solids. The apparent surface area and the micropore volume increase only slightly up to the treatment temperature of 500°C, increase greatly up to 800°C and decrease at higher temperatures.
Keywords: biomass; chars; holm-oak; pyrolysis; wood.